Dietary salt reduction for control of hypertension - Tjan, Richard (Faculty of Medicine, Trisakti University, 2011)
In developed as well as developing countries, the four main factors affecting blood pressure are high salt intake, low potassium intake, overweight, and low physical activity level. This is also true for the increase in blood pressure with advancing age, occurring in all societies. It is now accepted that excess dietary salt raises blood pressure levels, whereas dietary salt reduction reduces blood pressure and prevents vascular complications.(1) The effect of salt on blood pressure is presumably due to the inability of the kidneys to excrete large amounts of salt, as humans are evolutionary adapted to ingest and excrete less than 1 gram of salt per day.(2) In this connection it should be noted that the more important element in common salt (sodium chloride) is the sodium ion, and any restrictions applying to common salt also apply to all food items that contain sodium ions, such as sodium glutamate and baking soda.